Creating Sustainable Competitive Advantage Through Service Innovation: A Case Study Of Poslaju In Pos Malaysia Berhad - Md Yussoff, Yusliza (2014)
POS Malaysia Berhad is a premier postal service provider in Malaysia. POS Malaysia Berhad provides postal services throughout Malaysia; handling million of mail and items per day through a network of over 1,000 touch points countrywide includes Pos Malaysia Outlets, Pos Minis, Pos24 (Self-service Terminal), Post-On-Wheels (Mobile Outlets), postal agents and stamp agents. The evolution of technology over the years saw the emergence of digital media or internet changing the customer behaviours. According to annual report 2013, POS Malaysia Berhad service changed from traditional postal services to becoming one-stop provider of communications,